Research on the application of knowledge graph in intelligent operation and maintenance for optical transport network - YANG Ganggang; SHAO Zhugui; SHANG Fengliang; XU Jianrong; LIU Cui (Dianxin kexue)
In order to solve the problems of high cost, low efficiency, and weak intelligence in the traditional operation and maintenance mode of optical transport networks, the research status and challenges of knowledge graph technology in the telecom industry were analyzed. Firstly, an intelligent operation and maintenance system architecture for optical transport networks based on knowledge graphs were proposed. Key technologies such as network state perception, knowledge graph construction, and open search capabilities were emphatically studied. Secondly, the application of intelligent cutover in a city branch of China Telecom was taken as an example, the application effect was analyzed, and the test showed that the cutover efficiency was improved by about 3 times. Finally, the development trend of intelligent operation and maintenance of optical transmission networks based on knowledge graphs was discussed.